Patient-Reported Outcomes of Surgically Treated Insertional Achilles Tendinopathy. (December 2021) - Hörterer, Hubert; Oppelt, Sonja; Böcker, Wolfgang; Gottschalk, Oliver; Harrasser, Norbert; Walther, Markus; Polzer, Hans; Baumbach, Sebastian Felix
Background: The aim of this study was to assess the patient-reported outcome measures (PROMs) in patients with insertional Achilles tendinopathy (IAT) treated surgically by debridement of all pathologies through a midline-incision trans-achillary approach (MITA). Methods: This is a retrospective cohort study with current follow-up. Patients treated surgically by a MITA, addressing all pathologies of IAT, with at least 12 months of follow-up were included. Demographics, medical history, surgical details, and complications were recorded. Patient-reported outcomes were assessed using the Foot Function Index (FFI), Victorian Institute of Sport Assessment–Achilles questionnaire (VISA-A-G), visual analog scale foot and ankle (VAS-FA), and 12-Item Short-Form Health Survey (SF-12). Longitudinal FFI data were available for 48% of the patients. Results: A total of 118 patients (63.4%) with a mean follow-up of 50 ± 25 months were included. The FFI improved from 53 (24) preoperatively to 2 (11) points at the final follow-up. The final VISA-A-G score was 93 (26), the VAS-FA score 93 (15), the SF-12 Physical Component Summary 56 (8), and the SF-12 Mental Component Summary 55 (12) points. There was an additional FFI improvement between 12 months and the final follow-up. Up to 47% (VISA-A-G) of patients had residual symptoms. A postoperative shoe conflict was the only parameter negatively affecting the PROMs ( P < .001). Conclusion: Addressing all pathologies of IAT by the MITA resulted in overall good postoperative PROMs after 4 years. But up to 47% of patients remained impaired. The only parameter correlating with an impaired PROM was a postoperative shoe conflict. Level of Evidence: Level IV, retrospective cohort study.